Value-chain development for rural poverty reduction: A reality check and a warning - Stoian, Dietmar; Donovan, Jason; Fisk, John; Muldoon, Michelle F. (International Food Policy Research Institute, 2016)
This chapter draws attention to the link between VCD and smallholder livelihood strategies that comprise a complex mix of subsistence and market-oriented activities and that are diversified to meet multiple livelihood goals and mitigate risks; and the authors address the related implications for the design and assessment of value-chain interventions. They question some of the underlying assumptions of NGOs, government agencies, and private-sector agents seeking to link smallholders to higher-value markets.